Pengembangan Media Pembelajaran Berbasis IT Berbantuan Canva dan Liveworksheet pada Materi Pecahan - Al Ashari, Iqbal Ma'ruf; Qohar, Abd. (JUMAT: Jurnal Matematika, 2024)
Technology and information are developing massively and unstoppably. The development of information technology also leads to all fields in life, one of which is the field of education. Information technology can also be used as learning media in mathematics subjects. This research aims to develop IT-based learning media assisted by Canva and Liveworksheet on fraction material. This type of research is development research with the subject of 12 students of class B S-2 mathematics education. This research uses qualitative and quantitative data. Qualitative data comes from the results of input and suggestions given to researchers. Meanwhile, quantitative data comes from the validation sheet filled out by media experts, material experts, and user questionnaires, namely mathematics learning media lecturers and students during peer teaching activities in the classroom. The result of this research is that the developed media allows students to be actively involved in learning activities in the classroom. In addition, the learning media is also displayed interestingly and encourages students to improve their understanding of fraction material. The learning media developed is included in the valid category with an average score of ≥3 in each aspect assessed. And it is said to be feasible with a percentage of feasibility ≥75% in each aspect assessed.